Effect of salicylic acid and yeast extract on caffeic acid derivatives production in Echinacea purpurea L. - Mohammad Abdoli; Zhila Mehrpooya; Mohammad Reza Talebian (Institue of Medicinal Plants, ACECR, 2021)
Background: Purple coneflower, Echinacea purpurea (L.) Moench, has long been used in herbal remedies to prevent and treat a wide range of diseases like common cold, simple cough, pulmonary infections, dermatologic disorder and chronic diseases due to immunodeficiency. Objective: The present study was conducted to investigate the effects of salicylic acid and yeast extract foliar application on caffeic acid derivatives production in coneflower. Methods: Two factorial experiments were performed individually under greenhouse conditions during the years 2017-2018. In the first experiment, the effect of salicylic acid (0, 80, 160 and 320 mg/L) and each at four exposure times (24, 48, 72 and 96 hours) was studied. Also, in the second experiment, the effect of yeast extract (0, 0.75, 1 and 1.5 g/L) and each at four exposure times was investigated. Results: The results indicated that main effects and interactions of different concentrations of salicylic acid and yeast extract at different exposure times on caffeic acid derivatives content were significant (P ˂ 0.01). The highest cichoric acid, caftaric acid and echinacoside production was obtained after 96 hours of treatment at 160 mg/L salicylic acid treated plants. The highest cichoric acid production 7.150 mg/g DW was obtained after 96 hours of treatment at 1.5 g/L yeast extract treated plants, this was 3.58-fold higher compared to respective control. The lowest level of caffeic acid derivatives production was observed in control plants. Conclusion: In conclusion, salicylic acid and yeast extract foliar application have a positive effect on caffeic acid derivatives production in Echinacea purpurea aerial parts.